Tingkat Partisipasi Masyarakat Terhadap Pembangunan Infrastruktur Jalan di Desa Tana Toro - Dahariah, Dahariah (Universitas Gajah Putih, 2025)
This study aims to determine the level of community participation in road infrastructure development in Tana Toro Village. The location of this research was conducted in Tana Toro Village using a quantitative approach. The population and sample in the study were 85 Musrembang participants in Tata Toro Village. In data collection, the author used observation, interviews, questionnaires and documentation. The collected data were then analyzed using frequency and percentage tables. The results of the study showed that the participation of the Tana Toro Village community in the construction of road infrastructure was good at 64.78% seen from the indicators of Manipulation 74.50%, Therapy 69.50%, Informing 63.50%, Consultation 65%, Placation 86.25%, Partnership 62.50%, Delegated Power 55% and Citizen Control 42% while the factors influencing community participation in the construction of road infrastructure in Tana Toro Village were in the less good category of 56.69% seen from the supporting factors, namely the awareness/willingness factor 63.75%, the influence of others 63%, and government support 70.50% while the inhibiting factors were low education levels 50% and low income 45.25%.